Standard Cosmological Models with \(Λ\) > 0 Can Best Approximate our Universe - Paulo Aguiar (New Trends in Physical Science Research Vol. 2, 2022)
Recent observations in supernovae seem to leave no doubt among researchers that the Universe is in accelerated expanding. These conclusions are contrary to the convictions of most cosmologists and the presence of the positive cosmological constant solves this question. In this study, we show that by adding a positive value to the cosmological constant, traditional cosmological models can accurately describe our universe without the necessity for cold dark matter. We further highlight that objects moving faster than light speed in the Universe are physically possible without violating Einstein’s postulates.